Green Synthesis Nanopartikel Perak Menggunakan Ekstrak Daun Pepaya (Carica papaya L.) - Sefelin Sefelin; Sri Royani; Dian Islamiyati (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Papaya (Carica papaya L.), a plant commonly found in Indonesia, holds potential as an active ingredient in the pharmaceutical field, particularly in the environmentally friendly synthesis of silver nanoparticles. This study explores the ability of papaya leaf extract to act as a natural reducing agent through a green synthesis method, utilizing the flavonoid content it contains. The extract, obtained through an infusion process, was mixed with a 5 mM AgNO₃ solution at a specific ratio, and the formation of nanoparticles was indicated by a change in the solution’s color. Measurement using UV-Vis spectrophotometry at a wavelength of 350 nm showed a maximum absorbance value of 0.684, confirming the formation of silver nanoparticles. Thus, papaya leaf extract is proven to function effectively as a bioreductor in the synthesis process. Green synthesis offers a green alternative for the production of silver nanoparticles that is safer and more environmentally friendly. This research demonstrates great potential in the development of sustainable green technology in Indonesia by utilizing abundant natural resources. The results of this research can serve as a basis for further development in the application of silver nanoparticles in the fields of pharmacy and health, as well as increasing the economic value of papaya plants (Carica papaya L.). This also open up new opportunities for further research.